2020
DOI: 10.3389/fneur.2019.01421
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Structural Brain Connectivity of Young Healthy Individuals With High Trait Anxiety

Abstract: Results: Different connections were detected in fractional anisotropy-and fiber numberweighted networks. These connections were widely distributed in various regions, where relative significance was located in the inter-hemispheric frontal lobe, the frontallimbic lobe in the right intra-hemisphere, and the frontal-temporal lobe in the ipsilateral hemisphere. However, no significant difference was found in fiber length-weighted network and in graph properties among the three networks. Conclusions: The structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“… Baumgartner et al (2018) detected that cognitive deficits imposed by stroke were closely related to disruption of hippocampal-thalamic connectivity. Furthermore, a fMRI study of a highly anxious population indicated aberrant connectivity of the left hippocampus and thalamus ( Yang et al, 2019 ). Research has demonstrated that the connectivity between the hippocampus and thalamus affects depression to a large degree ( Im et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… Baumgartner et al (2018) detected that cognitive deficits imposed by stroke were closely related to disruption of hippocampal-thalamic connectivity. Furthermore, a fMRI study of a highly anxious population indicated aberrant connectivity of the left hippocampus and thalamus ( Yang et al, 2019 ). Research has demonstrated that the connectivity between the hippocampus and thalamus affects depression to a large degree ( Im et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we relied on a relatively small sample size. While our sample size was similar to that of recent neuroimaging studies, future studies including a larger sample size would be helpful in demonstrating confident results [ 60 , 61 ]. Third, 55 patients were consuming antidepressants during the study, and several studies have found a relationship between structural changes of the brain and antidepressant treatment [ 62 ].…”
Section: Discussionmentioning
confidence: 84%
“…At the cortex, the ventral anterior insula is responsible for integrating information from subcortical and cortical regions ( Craig et al, 2009 ; Nagai et al, 2010 ), using that information to detect salient events, and facilitate resource allocation in other attentional networks to guide proper response ( Menon and Uddin, 2010 ). Connectivity between the ventral anterior insula and medial orbitofrontal cortex has been directly associated with anxiety behaviors ( Kim et al, 2012 ; Simmons et al, 2013 ; Yang et al, 2020 ), which are driven by enhanced error monitoring, likely mediated by the basolateral amygdala, and a tendency to rely on reactive control strategies ( Braver, 2012 ; Moser et al, 2013 ). In this study, we observed increased functional connectivity in this circuit that was associated with greater head-to-ball impact exposure and diminished proactive control.…”
Section: Discussionmentioning
confidence: 99%